Spatial variability of rainfall in urban catchment - Haris H.; Chow M.F.; Sidek L.M. (Springer, 2023)
Catchments; Rain; Rain gages; Runoff; Sewage; Systematic errors; ANOVA analysis; Boxplot analysis; Rainfall analysis; Spatial variability; Urban runoff; Hydrological modeling; Rapid urbanization process; Statistical differences; Statistically significant difference; Analysis of variance (ANOVA)